Coesão relacional e mecanismos formais e informais de coordenação em redes de supermercados de pequeno porte no estado de São Paulo - Garcia, Luciano Mitidieri Bento (Universidade Federal de São Carlos, 2011)
In the supermarket segment, which is in a growing process of concentration, there are small businesses, mostly on the periphery of cities and dealing with the treatment of lower income populations. These independent businesses have faced their challenges through cooperative actions in the form of central business. Initially focused on the increased bargaining power with suppliers through joint procurement, the central business begin to generate other benefits for its members as an exchange of information and experiences and for synergies through shares in other business areas such as selection, training and human resource management, accounting, marketing actions, etc.. The central business of small supermarkets can be defined as horizontal interorganizational cooperative networks whose effectiveness was associated with the operation and strength of its formal and informal mechanisms of coordination and relational cohesion among its members. This work aimed to study and analyze a group of these networks located within the state of S. Paul compared in terms of its effectiveness, relations between members and the mechanisms through which they coordinate their activities in each network. It was also made an analysis of the dynamic effects of a merger between two networks occurred recently. It was found that, for the networks studied, concerning the aspect of its operations and its process of formation and consolidation, there is evidence of similarities between them in setting up an isomorphic process and the interaction between formality and informality. Moreover, there remain some differences in coordination and cohesion that would be associated.
Keywords: Engenharia de produção; Redes de empresas; Novo institucionalismo; Eficácia organizacional; Canais de distribuição; Pequenas e médias empresas; Supermercados; Centrais; Cooperação; Coordenação; Coesão; Supermarkets; Central business; Cooperation; Institutionalism; Networks; Coordination; Cohesion; Effectiveness; ENGENHARIAS::ENGENHARIA DE PRODUCAO